Comparative evaluation of novel African swine fever virus (ASF) antibody detection techniques derived from specific ASF viral genotypes with the OIE internationally prescribed serological tests - Gallardo, C.; Soler Garzón, Alvaro; Nieto, R.; Carrascosa, A.L.; Mia, G.M. de; Bishop, Richard P.; Martins, C.; Fasina, F.O.; Couacy-Hyman, E.; Heath, L.; Pelayo, V.; Martin, E.; et al. (Elsevier, 2013)
The presence of antibodies against African swine fever (ASF), a complex fatal notifiable OIE disease of swine, is always indicative of previous infection, since there is no vaccine that is currently used in the field. The early appearance and subsequent long-term persistence of antibodies combined with cost-effectiveness, makes antibody detection techniques essential in control programmes. Recent reports appears to indicate that the serological tests recommended by the OIE for ASF monitoring are much less effective in East and Southern Africa where viral genetic and antigenic diversity is the greatest. We report herein an extensive analysis including more than 1,000 field and experimental infection sera, in which the OIE recommended tests are compared with antigen-specific ELISAs and immuno-peroxidase staining of cells (IPT). The antibody detection results generated using new antigen-specific tests, developed in this study, which are based on production of antigen fractions generated by infection and virus purification from COS-1 cells, showed strong concordance with the OIE tests. We therefore conclude that the lack of success is not attributable to antigenic polymorphism and may be related to the specific characteristics of the local breeds African pigs.